Asesmen Perkembangan Kognitif Anak Usia 5–6 Tahun Menggunakan Skala Penilaian dengan Tema Alat Transportasi - Massayu Anastasia Sihotang; Yusnita Meizarah; Moutia Suri Wahda; Audi Asyahfira; Tri Cintami Gaberela (Lembaga Pengembangan Kinerja Dosen, 2025)
Assessment is a systematic process to collect and analyze information about child development, which is an important basis for planning, monitoring, and evaluating learning activities in early childhood education. Cognitive development includes children's ability to think, understand the environment, solve problems, and process information. This study aims to describe the results of cognitive development assessments of children aged 5–6 years using an assessment scale compiled based on cognitive development indicators. This study uses a quantitative method that aims to describe the results of cognitive development assessments using an assessment scale. The results of the assessment showed that all children were in the categories of Developing Well Towards Expectations (BSH) and Developing Very Good (BSB) in the four indicators of cognitive development observed. There are no children in the Not Developing (BB) or Starting to Develop (MB) categories.